Females Paired with New and Heavy Mates Reduce Intra-Clutch Differences in Resource Allocation - Poisbleau, Maud (Public Library of Science, 2013)
Reproductive investment affects both offspring and parental fitness and influences the evolution of life histories. Females may vary their overall primary reproductive effort in relation to the phenotypic characteristics of their mate. However, the effects of male quality on differential resource allocation within clutches have been largely neglected despite the potential implications for mate choice and population dynamics, especially in species exhibiting biparental care and brood reduction. Female southern rockhopper penguins Eudyptes chrysocome paired with heavy mates reduced intra-clutch variation in egg and albumen masses. Females paired with new mates also reduced intra-clutch variation in yolk androgen levels. Since both an increased mass and increased androgen concentrations positively influence chick survival under sibling competition, the chances of fledging the whole clutch are likely to be higher for newly formed pairs with heavy males than for previously formed pairs with light males. Interestingly, total clutch provisioning did not vary with male quality. We show for the first time that females vary intra-clutch variation in resource allocation according to male quality. In species with brood reduction, it may be more adaptive for females to modulate the distribution of resources within the clutch according to breeding conditions, than to change their total clutch provisioning.